Mainstreaming Religious Moderation in Male Tradition of the Balinese Muslim Community - Made Saihu; Athoillah Islamy (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2022)
The plural societies, on the one hand, are an asset. However, it can also lead to social conflict. This study aims to uncover the values of moderatism found in the Male tradition in Jembrana, Bali. This article is qualitative research with an interpretive method. The data were collected through observation and interviews. This study reveals that there are values of religious moderation found in the Male tradition practiced by the Muslim community in Jembrana, Bali. The tradition contains integration between Islamic teachings and traditions that do not conflict with the normative teachings of Islam. The tradition involves not only the Muslims but also the Hindus. Thus, the social harmony and co-existence among religious believers are firmly established through Male tradition. This study expectedly contributes to giving more references for mainstreaming religious moderation based on the factual case in Indonesia. Theoretically, it also supports the government’s formulation of the indicators of religious moderation in creating a harmonious relationship among believers through local tradition preservation. Yet, this study has not explained the concrete strategy taken by the Jembrana local government regarding the success of mainstreaming religious moderation in the practice of Male tradition.